Improving Students’ Reading Comprehension of Descriptive Texts through Cognitive Strategy at Grade VII-2 of SMPN I Indra Praja Tembilahan - Adam, Adam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This research aimed to (1) know whether or not cognitive strategy can increase students’ skill in writing descriptive texts, and (2) know what factors can influence the increasing of those writing skills. This research categorized as action research which conducted in two cycles. Each cyles consisted of four times meeting. Each of them composed of plan, action, observation, dan reflection. The participant in this research was all 22 students of VII-2 SMPN I Indra Praja Tembilahan. The data was collected from (1) Observation sheet; students, teacher, lesson procedures/plan, (2) Field note, (3) Interview, and (4) Writing test. It was found in this research that the use of cognitive strategy can increase students’ skill in writing descriptive texts. The finding of this research shown that there was an increasing of students’ mean score above minimum criteria of minimum learning mastery standard (75).The factors that influenced students’ skill in writing descriptive text were (1) reading material given to students,(2) students’ motivation, and (3) teachers’ approach to students. It can be concluded that the application of cognitive strategy in teaching reading descriptive texts gave positive results shown by the increasing of students’ skill in reading descriptive texts.